Barriers to adoption of optimal complementary feeding practices in Ethiopia: A formative qualitative investigation: Evidence from SPIR II - Leight, Jessica; Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Mulford, Michael; Tadesse, Elazar (International Food Policy Research Institute, 2022)
Since its inception in 2005, the Productive Safety Net Program (PSNP) has been a cornerstone of the Ethiopian government’s strategy for poverty alleviation, disaster risk management, and rural development. The PSNP provides food or cash transfers targeted to poor households in the form of payments for seasonal labor on public works or as direct support to households. It has played an important role in improving the lives of poor Ethiopian households by reducing household food insecurity, increasing asset holdings, and improving agricultural productivity (Berhane et al. 2014; Hoddinott et al. 2017).